Stand off bomb detection using neutron interrogation - Lowrey, Justin (Kansas State University, 2008)
One of the most pressing threats facing the United States is the increasingly effective use of improvised explosive devices or IEDs. Many commonly used techniques to detect explosives involve imaging. The primary drawback of imaging is that it requires interpretation of one or more images from each target. Human interpretation requires extensive training and is subject to the chance of false-negatives due to human fatigue. To counter the threat posed by IEDs, the signature-based radiation scanning (SBRS) technology has been developed. The goal of this project is to create an automated system, with minimal operator assistance, that is capable of detecting at least a gallon-sized explosive sample from at least one meter away. It is hoped that this can be accomplished quickly, in less than 30 seconds, with high sensitivity and specificity. The SBRS technique is based on the fact that many classes of materials have similar stoichiometries. For example, many common explosives have characteristic concentrations of hydrogen, carbon, nitrogen and oxygen. As neutrons interact with a material, unique gamma rays are created based on the composition of the material. Specifically, in this work, the gamma rays from inelastically scattered neutrons and from thermal neutron capture are investigated. Two neutron detectors are also used, whose responses depend on neutron thermalization in and around the target. Response templates are created based on gamma-ray and neutron responses that are collected from targets that contain explosives,. These templates are developed under different conditions for many different explosive materials to create a library of templates. The collection of responses from an unknown target is compared to a subset of the library of templates using a figure of merit to distinguish benign from explosive targets. Preliminary experiments were performed at Kansas State University. A high-purity germanium detector (HPGe) was used to detect the gamma rays. Two neutron detectors, one covered with cadmium, were used to detect back-streaming neutrons. A 252Cf radioisotope source as well as a Triga Mk III reactor were used as neutron sources.
Keywords: Explosive; Detection; Engineering, Nuclear (0552)